Sharar's Novel Dilchasp: One Penny Too Many - Muhammad Naeem (بازیافت)
Colonial predicament made the life and its understanding complex in the Subcontinent. To represent this complexity, Urdu writers found the polyphonic genre, i.e. the novel helpful. They used different techniques of characterization to narrate the social hierarchy of characters. The novel also provided the space for them to attract the people with encapsulating the residual sensibility of conventional love of Urdu poetry and at the same time launch their ideas of reform to accommodate the changing world. This article presents an analysis of Sharar's Dilchasp and argues that he used the novelistic genre to represent his hierarchized social milieu, cultural norms and reformative agenda.